2021
DOI: 10.7554/elife.67587
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injury compromises nucleocytoplasmic transport and leads to TDP-43 pathology

Abstract: Traumatic brain injury (TBI) is a predisposing factor for many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), Alzheimer’s disease (AD), Parkinson’s disease (PD), and chronic traumatic encephalopathy (CTE). Although defects in nucleocytoplasmic transport (NCT) is reported ALS and other neurodegenerative diseases, whether defects in NCT occur in TBI remains unknown. We performed proteomic analysis on Drosophila exposed to repeated TBI and identified resultant alterations in several no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 107 publications
6
33
0
Order By: Relevance
“…We found a strong consensus that TDP-43 pathology is elevated and widespread in CTE compared to normal aging and AD cases. All four studies reported that TDP-43 aggregation is absent in normal aged cases but present in spinal cord, hippocampus, amygdala, frontal cortex, medial temporal lobe, and/or basal ganglia of CTE cases [ 5 , 49 , 59 , 60 ]. One study showed that TDP-43 inclusions were more abundant and widespread in CTE than AD, with a distribution more closely resembling FTD with TDP-43 inclusions [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a strong consensus that TDP-43 pathology is elevated and widespread in CTE compared to normal aging and AD cases. All four studies reported that TDP-43 aggregation is absent in normal aged cases but present in spinal cord, hippocampus, amygdala, frontal cortex, medial temporal lobe, and/or basal ganglia of CTE cases [ 5 , 49 , 59 , 60 ]. One study showed that TDP-43 inclusions were more abundant and widespread in CTE than AD, with a distribution more closely resembling FTD with TDP-43 inclusions [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proteins involved in nuclear pore complex and nucleocytoplasmic transport contribute to the regulation of protein synthesis. Disruptions to the nuclear pore complex have been reported in other neurodegenerative diseases, but only one study investigated this in CTE postmortem tissue [ 5 ]. Nuclear pore glycoprotein p62 (NUP62) is an essential component of the nuclear pore complex and immunoreactivity for NUP62 was found to be increased in CTE tissue compared to normal age-matched cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using Drosophila models to investigate the link between repetitive brain trauma and ALS show that Drosophila have implicated disruptions to altered protein clearance, autophagy pathways, and nucleocytoplasmic transport [175,176]. In Drosophila expressing C9orf72, repetitive brain trauma showed increased mortality and locomotor dysfunction [175], which may be explained by TBI altering protein clearance pathways such as the ubiquitin-proteosome system or autophagy pathway.…”
Section: Tdp-43 Traumatic Brain Injury and Chronic Traumatic Encephalopathymentioning
confidence: 99%
“…Noteworthy, SQSTM1/p62 is an autophagy receptor and has been identified as a rare genetic variant in both ALS and FTD in addition to being able to activate the NF-κβ pathway [72]. In a further follow up study by Anderson and colleagues, proteomics analysis of Drosophila brains following repetitive trauma demonstrated that repetitive TBI upregulated nuclear pore proteins, altered nucleoporin stability, nucleocytoplasmic trans-port proteins, and nucleocytoplasmic transport itself [176]. Interestingly, this upregulation led to TDP-43 mislocalisation, aggregation, and phosphorylation in addition to decreased motor function and lifespan.…”
Section: Tdp-43 Traumatic Brain Injury and Chronic Traumatic Encephalopathymentioning
confidence: 99%